2013
DOI: 10.1038/emboj.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

Eps8 controls dendritic spine density and synaptic plasticity through its actin-capping activity

Abstract: Actin-based remodelling underlies spine structural changes occurring during synaptic plasticity, the process that constantly reshapes the circuitry of the adult brain in response to external stimuli, leading to learning and memory formation. A positive correlation exists between spine shape and synaptic strength and, consistently, abnormalities in spine number and morphology have been described in a number of neurological disorders. In the present study, we demonstrate that the actinregulating protein, Eps8, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 95 publications
(153 reference statements)
2
66
0
Order By: Relevance
“…Further support for this hypothesis comes from the evidence that reduced TrkB-mTOR signaling is associated with a significant decrease in protein expression of the excitatory synaptic marker PSD-95 in patients with idiopathic autism [132], suggesting fewer excitatory synapses. Lastly, knockout of the TrkB-activated actin-capping molecule Eps8 results in widespread abnormalities in spine morphology and function, decreased LTP and autism-like symptoms [115]. Taken together, these data support the model that defective TrkB-mTOR signaling disrupts spine density, morphology and function, hence playing a key role in aberrant connectivity during development and thereby in the etiology of autistic traits.…”
Section: De-regulated Mtor Dendritic Spines and Synaptic Transmissionsupporting
confidence: 63%
See 3 more Smart Citations
“…Further support for this hypothesis comes from the evidence that reduced TrkB-mTOR signaling is associated with a significant decrease in protein expression of the excitatory synaptic marker PSD-95 in patients with idiopathic autism [132], suggesting fewer excitatory synapses. Lastly, knockout of the TrkB-activated actin-capping molecule Eps8 results in widespread abnormalities in spine morphology and function, decreased LTP and autism-like symptoms [115]. Taken together, these data support the model that defective TrkB-mTOR signaling disrupts spine density, morphology and function, hence playing a key role in aberrant connectivity during development and thereby in the etiology of autistic traits.…”
Section: De-regulated Mtor Dendritic Spines and Synaptic Transmissionsupporting
confidence: 63%
“…The Eps8 pathway signals through Rac, which stabilizes dendritic spines, and is opposed by Rho, which destabilizes spines [154]. We found significantly decreased Eps8 in autism vs. control fusiform gyrus [115], suggesting an imbalance in the Rac/Rho pathway influencing spine density and maturation. Together with decreased Eps8/Rac signaling, increased proBDNF in autism, acting through p75 NTR to activate Rho, may unbalance the Rac/Rho pathway.…”
Section: Decreased Catalytic Trkb and Trkb Signaling In Idiopathic Aumentioning
confidence: 66%
See 2 more Smart Citations
“…It has been shown that this procedure results in significant increase in the size of PSD-95-positive puncta and in a higher extent of colocalization of PSD-95 and v-Glut1 staining, in line with a potentiation of synaptic connections. 31 To univocally ascribe the lack of potentiation to postsynaptic defects, we tested the ability of wt-GFP neurons cultured together with Het neurons (wt-GFP/Het) or Het neurons cultured together with wt-GFP neurons (Het/wt-GFP) (Figures 3j and k) to undergo synaptic potentiation. These experiments indicated that wt-GFP neurons receiving synaptic inputs from SNAP-25 Het neurons, when subjected to a chemical LTP protocol, displayed potentiation levels that were similar to their control counterparts.…”
Section: Resultsmentioning
confidence: 99%